Super-resolution Reconstruction MRI Application in Fetal Neck Masses and Congenital High Airway Obstruction Syndrome. Issue 4 (October 2021) - Mufti, Nada; Ebner, Michael; Patel, Premal; Aertsen, Michael; Gaunt, Trevor; Humphries, Paul D.; Bredaki, Fonteini Emmananouella; Hewitt, Richard; Butler, Colin; Sokolska, Magdalena; Kendall, Giles S.; Atkinson, David; et al.
Objective: Reliable airway patency diagnosis in fetal tracheolaryngeal obstruction is crucial to select and plan ex utero intrapartum treatment (EXIT) surgery. We compared the clinical utility of magnetic resonance imaging (MRI) super-resolution reconstruction (SRR) of the trachea, which can mitigate unpredictable fetal motion effects, with standard 2-dimensional (2D) MRI for airway patency diagnosis and assessment of fetal neck mass anatomy. Study Design: A single-center case series of 7 consecutive singleton pregnancies with complex upper airway obstruction (2013-2019). Setting: A tertiary fetal medicine unit performing EXIT surgery. Methods: MRI SRR of the trachea was performed involving rigid motion correction of acquired 2D MRI slices combined with robust outlier detection to reconstruct an isotropic high-resolution volume. SRR, 2D MRI, and paired data were blindly assessed by 3 radiologists in 3 experimental rounds. Results: Airway patency was correctly diagnosed in 4 of 7 cases (57%) with 2D MRI as compared with 2 of 7 cases (29%) with SRR alone or paired 2D MRI and SRR. Radiologists were more confident ( P = .026) in airway patency diagnosis when using 2D MRI than SRR. Anatomic clarity was higher with SRR ( P = .027) or paired data ( P = .041) in comparison with 2D MRI alone. Radiologists detected further anatomic details by using paired images versus 2D MRI alone ( P < .001). Cognitive load, as assessed by the NASA Task Load Index, was increased with paired or SRR data in comparison with 2D MRI. Conclusion: The addition of SRR to 2D MRI does not increase fetal airway patency diagnostic accuracy but does provide improved anatomic information, which may benefit surgical planning of EXIT procedures.